Abu Dehbel's poetical approaches - Abde Ali Feizoullahzadeh; Aboulfazl Rezaee (دراسات في اللغة العربيّة وآدابها)
This paper examines the types of literary lyric poets of the Umayyad era, Abu Dehbel Al Jomahi. He was known for his full commitment to the principles of Islam and good morals, and was a man of virtue. As the book Al-Aqani cites he exposed himself to thirst and hunger to the verge of death but his passion could not force him to commit the divine prohibitions. He is mentioned in all religious narratives, as a pious and devotee poet to Ahl-i-Bait. Islam was revealed in his comportment, life and his relation to his society. Abu Dehbel's lyricism for Atekah, the daughter to Mo'aviah, has allocated much of his biography in Al-Aqani. From what the owner of the book Al-Aqani has narrated, we can conclude that Abu Dehbel's lyricisim for Atekah, shows a pivotal truth and his hatred from Umayyads and his insistence on oppositions and enmity to them. Thus, his lyrics for Atekah is somehow a type of lyrics called "rebellion lyric". After introducing Abu Dehbel's lyric samples, we have turned to some samples of his poetry which show his poetical approaches, noting that it is hard to put him, as one of the five famous poets of Qoraish, under any of approaches and this issue is a matter of preference and not based on certainty.